Strategic Management and Innovation in Curriculum Development - Nurhasanah, Enung; Lasmanawan, I Wayan; Suharta, I Gusti Putu; Widiana, I Wayan (Journal of English Language and Education, 2025)
This study focuses on curriculum innovation, exploring its key characteristics and the processes involved in its development. As the foundational document that outlines educational goals, learning objectives, and instructional methods, the curriculum plays a vital role in shaping the quality of education. In the context of globalization and rapid scientific and technological advancement, it is essential that curricula be continuously revised to remain relevant and capable of producing competitive and future-ready human resources. Without a well-structured curriculum, achieving educational objectives becomes exceedingly difficult. This study employs a qualitative approach using literature review and content analysis, involving systematic stages of data presentation, reduction, verification, and conclusion drawing. From the analysis, four conceptual approaches to curriculum innovation are identified: (1) the helpful approach, which addresses the need for physical infrastructure to support new learning materials; (2) the instructional approach, which emphasizes the importance of equipping educators with adequate understanding and skills to implement innovations; (3) the persuasive approach, aimed at encouraging stakeholders to support curriculum changes through communication and engagement; and (4) the coercive approach, which uses policy or authority-driven mandates to enforce necessary adjustments. Given the constantly evolving demands of society, a flexible, contextualized, and responsive curriculum is crucial. Educational institutions must therefore engage in continuous curriculum development grounded in situational analysis and real-world needs to ensure alignment with the changing educational landscape.